Exploring the potential of digital biomarkers as a measure of brain health ‘capital’ - Dylan Powell; Stephanie A. Adams; Donncha Mullin; Miles Welstead; John E. Harrison; Craig Ritchie (npj Digital Medicine)
Neurological conditions, including dementia, pose a major public health challenge, contributing to a significant and growing clinical, economic, and societal burden. Traditionally, research and clinical practice have focused on diseases like dementia in isolation. However, in an ageing, multimorbid population, this approach is becoming increasingly inadequate. Recognising brain health as a lifelong attribute influenced by various health determinants, this paper explores the concept of brain health, identifies key challenges in assessing it effectively, and examines how digital biomarkers could provide a versatile measurement framework to enhance monitoring and facilitate earlier intervention. Finally, we outline future directions to help advance definitions of meaningful aspects of brain health integration, and practical adoption of digital biomarkers, enhancing our capacity to measure and preserve ‘brain health capital’ or ‘brain span’ across the lifecourse.